A preparation method of a flexible electromagnetic shielding material based on a composite of two-dimensional titanium carbide and aramid fiber
By uniformly adhering MXene material on aramid fibers, using the self-polymerization characteristics of dopamine, the problem of insufficient flexibility and mechanical properties of existing electromagnetic shielding materials was solved, and an efficient aramid-MXene composite material was prepared, suitable for aerospace and military use. Engineered and flexible wearable devices.
Patent Information
- Application Number
- CN202210127581.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-02-11
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2042-02-11
AI Technical Summary
Existing electromagnetic shielding materials have shortcomings in flexibility and mechanical properties, especially in the fields of aerospace, military engineering and flexible wearable electronic devices, it is difficult to meet the requirements of high electromagnetic shielding efficiency and mechanical properties.
Using the self-polymerization of dopamine under alkaline conditions, two-dimensional titanium carbide (MXene) material is uniformly attached to the surface of aramid fibers. Combined with the flexibility and mechanical properties of aramid fibers, it is prepared to have both ultra-flexible, high strength and wide frequency. Aramid-MXene composite material with high electromagnetic shielding performance.
It realizes ultra-flexible and high-strength electromagnetic shielding material, which can display electromagnetic shielding performance of 20~85dB in the X-band, and is simple, safe and environmentally friendly, without toxic solvents, and is suitable for further processing into flexible electromagnetic shielding products of different forms.
Smart Images

Figure CN114635282B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of new process development of functional aramid fiber materials, and relates to a method for preparing an aramid-MXene composite material with flexible electromagnetic shielding performance. Background Art
[0002] Modern science and technology are developing rapidly. With the rapid development of high-power, high-density and high-integration technologies in electronic and communication equipment, the application of electromagnetic waves in the fields of electronics, electrical equipment, communication equipment, etc. can be seen everywhere. In the process of application, electromagnetic waves are likely to cause serious interference to nearby electronic instruments, precision instruments, communication signals, etc., especially with the rapid development and widespread application of the fifth generation (5G) and sixth generation (6G) communication technologies, related fields have put forward higher requirements for electromagnetic shielding materials. In addition, problems such as electromagnetic radiation, electromagnetic interference and information leakage have further restricted the development of aerospace, military engineering, communications, artificial intelligence and flexible wearable electronic devices. In order to ensure the operating reliability and information security of precision electronic components, reduce or even prevent the interference of electromagnetic waves, the most effective way in modern science and technology is to use electromagnetic shielding materials for electromagnetic protection.
[0003] Electromagnetic shielding mainly uses electromagnetic shielding materials to reflect electromagnetic waves. Electromagnetic shielding materials usually select high conductivity and high magnetic permeability materials. Traditional electromagnetic shielding materials include metals, alloys, etc., which are widely used in electromagnetic shielding materials due to their high conductivity and high electromagnetic shielding effectiveness. However, they have the disadvantages of high density, low flexibility, corrosion resistance, and bending fatigue resistance. The problem of bulky use has seriously restricted the further application and development of electromagnetic shielding materials. In recent years, polymer-based conductive composite materials composed of polymer matrix and conductive fillers (such as graphene, multi-walled carbon nanotubes, metal nanoparticles and nanowires and their hybrids) have the advantages of light weight, chemical corrosion resistance, easy processing and stable shielding performance, but have the disadvantages of low conductivity and poor electromagnetic shielding effectiveness. Since polymer-based conductive composite materials have very low conductivity, high filler content and large thickness are usually required to obtain ideal electromagnetic shielding performance, which leads to the decrease of mechanical properties (especially flexibility and strength) and processability. The higher thickness also brings the disadvantage of bulkiness, which is even inferior to traditional metal shielding materials.
[0004] Aramid is a synthetic aromatic polyamide fiber, the full name of which is "polyphenylene phthalate". As a rigid molecule, it has high molecular symmetry, crystallinity and glass transition temperature. These structural characteristics give it excellent properties such as high specific strength, high specific modulus, and fatigue resistance. At the same time, it has excellent properties such as light weight, permanent flame retardancy, resistance to organic solvents, and high temperature resistance. It has been widely used in aerospace, transportation, communications, high-temperature insulation, bulletproof protection and other national defense and civilian fields. It combines military value and economic value and is one of my country's key strategic material varieties. Aramid is divided into two categories: fully aromatic polyamide fiber and heterocyclic aromatic polyamide fiber. The fibers that have been industrialized in fully aromatic polyamide fibers are mainly para-aramid (PPTA) and meta-aramid (PMIA).
[0005] MXene is a new type of two-dimensional (2D) transition metal carbide and / or nitride nanomaterials. Due to its excellent metallic conductivity, hydrophilicity and good interfacial interaction with polymers, MXene is widely used in energy storage, strain sensing, electric heating, wave absorption (MA) and electromagnetic shielding. However, although MXene-based electromagnetic shielding materials have high electrical conductivity and high electromagnetic shielding effectiveness, their extremely poor flexibility and mechanical properties limit the application of this material in aerospace, military engineering, artificial intelligence and flexible wearable electronic devices.
[0006] Dopamine contains amino catechol, which is a catechol phenol neurotransmitter secreted by the brain and is also a raw material for preparing biomedical materials. In the past two decades, dopamine and its analogs have been widely used in the field of materials. In 2007, Messersmith found that dopamine (DA) can polymerize and form polydopamine (PDA) nanofilm on almost any solid surface when exposed to air under weak alkaline conditions (pH 8.5). This opened the door to polydopamine surface modified nanomaterials. Since polydopamine is actually an insoluble cross-linked polymer, there are relatively few research methods, and its polymer structure has not been very clear. However, after years of research, the mechanism by which dopamine can undergo oxidative self-polymerization under certain conditions has become increasingly clear: dopamine can cyclize to form indole, and then achieve continuous self-polymerization reaction through intermolecular polymerization and π-π stacking self-assembly of phenyl groups. Therefore, in this patent, the self-polymerization characteristics of dopamine are used to modify the surface of fiber materials to achieve new functions.
[0007] There are already public invention patents for composite materials made by mixing MXene and aramid fibers. For example, composite materials made by hot pressing have simple processes but many disadvantages. For example, aramid fabrics have very large porosity, so aramid fibers and MXene cannot be evenly combined during mechanical compression; melting fibers by hot pressing will seriously affect the flexibility of the fabric; the combination of MXene and aramid relies purely on van der Waals forces, so the bonding force is not strong, and it is very easy to peel off under washing, bending or other external forces, resulting in a decrease in electromagnetic shielding performance. In addition, the preparation method of the public invention patent in which aramid fibers are dispersed and then hot-pressed with silver nanowires and MXene materials can only obtain aramid paper and cannot be further processed into flexible electromagnetic shielding materials.
[0008] Therefore, the present invention creatively utilizes the high viscosity of dopamine and its self-polymerization under alkaline conditions to uniformly attach MXene materials to the surface of aramid fibers. Combining the flexibility and excellent mechanical properties of aramid fibers with the high electromagnetic shielding effectiveness of MXene materials, aramid-MXene electromagnetic shielding materials with ultra-flexibility, high strength, and broadband high electromagnetic shielding effectiveness can be simply and effectively prepared. Summary of the invention
[0009] In response to the problems existing in existing traditional metal electromagnetic shielding materials and polymer-based conductive filler composite materials, the present invention provides a method for preparing a flexible electromagnetic shielding material based on a composite of two-dimensional titanium carbide (MXene) and aramid fiber, which can simply and effectively prepare aramid-MXene electromagnetic shielding materials that are ultra-flexible, high-strength, wide-band and high electromagnetic shielding efficiency. The materials can be further processed into flexible electromagnetic shielding products in different forms and are widely used in aerospace, military engineering, artificial intelligence, flexible wearable electronic devices and other fields.
[0010] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0011] The present invention provides a method for preparing a flexible electromagnetic shielding material based on a composite of two-dimensional titanium carbide (MXene) and aramid fiber, comprising the following steps:
[0012] Step 1: Prepare a stable two-dimensional titanium carbide flake dispersion;
[0013] Step 2: Cleaning the aramid fiber;
[0014] Step 3: dissolving dopamine hydrochloride powder in water to prepare a dopamine hydrochloride solution of a certain concentration;
[0015] Step 4: adding the washed aramid fiber and the two-dimensional titanium carbide flake dispersion into the dopamine solution;
[0016] Step 5: Add pH buffer to adjust the pH value of the system so that dopamine forms linear polymers through free radical polymerization, and finally the aramid fiber is grafted onto the two-dimensional titanium carbide (MXene) sheet;
[0017] Step 6: Wash the aramid fiber and dry it to make aramid-MXene composite material
[0018] As the preferred technical solution:
[0019] According to the method described above, in step 1, the titanium aluminum carbide powder is vigorously stirred in the mixed acid solution to react, and the precipitate is centrifuged to remove the precipitate; deionized water is added to the precipitate and then centrifuged to wash the acid solution: the acid solution washing operation needs to be repeated more than five times until the pH value is between 6 and 7; a 20% lithium chloride aqueous solution is added to the precipitate, and it is vigorously stirred under ice water bath conditions, and centrifuged multiple times to make the pH greater than 6, and the supernatant is centrifuged to separate the two-dimensional titanium carbide thin film dispersed aqueous solution. Wherein, the mixed acid solution is a mixed solution of 12M hydrochloric acid, 49% hydrofluoric acid, and deionized water, and the volume ratio of 12M hydrochloric acid, 49% hydrofluoric acid, and deionized water is (3~8): (1~4): 1, and the ratio of titanium aluminum carbide powder, mixed acid solution, and lithium chloride aqueous solution is 1g: 100~200mL: 500~1000mL.
[0020] In the method described above, in step 2, the aramid fiber is para-aramid, meta-aramid or heterocyclic aramid; the cleaning method is to ultrasonically clean the aramid fiber with acetone, deionized water and isopropyl alcohol respectively, and then dry it.
[0021] In the method described above, in step 3, dopamine hydrochloride powder is added to deionized water, and the concentration of the dopamine hydrochloride solution is 2 mg / mL.
[0022] In the method as described above, in step 4, the concentration of the two-dimensional titanium carbide flake dispersion is 1-5 mg / mL, the mass ratio of dopamine to two-dimensional titanium carbide is 2:1-5, and the mass ratio of two-dimensional titanium carbide to aramid fiber is 1-5:100.
[0023] According to the method described above, in step 5, a pH buffer solution is added under magnetic stirring to raise the pH value of the solution to 8-8.5, and finally air is continuously introduced into the solution for a reaction time of more than 24 hours; wherein the pH buffer solution includes but is not limited to a tris(hydroxymethyl)aminomethane aqueous solution, a boric acid-sodium hydroxide aqueous solution, a potassium hydrogen phosphate-citric acid aqueous solution, a carmody buffer solution, an N-tris-(hydroxymethyl)methylaminoacetic acid aqueous solution and a tris(hydroxymethyl)methylaminopropanesulfonic acid aqueous solution, and the concentration range is 1%wt~20%wt.
[0024] In the method described above, in step 6, the aramid fiber is taken out and rinsed repeatedly with clean water for more than ten times until no black residue flows out; the drying temperature is 80~160 o C, drying time is 8~12 hours.
[0025] The electromagnetic shielding effectiveness of the aramid-MXene composite material prepared by the method described above is between 20 and 85 dB in the X-band (8.2 to 12.4 GHz).
[0026] The mechanism of preparing a stable two-dimensional titanium carbide flake dispersed aqueous solution in the present invention is as follows: through chemical treatment, the aluminum element in the titanium aluminum carbide powder is selectively corroded, the structure of the titanium aluminum carbide crystal is destroyed to form a stable titanium carbide flake structure; due to the presence of hydrophilic hydroxyl groups and the effect of charge, the peeled titanium carbide flakes cannot repolymerize, thereby forming a stable two-dimensional titanium carbide flake dispersed system in water.
[0027] In the present invention, due to the high Young's modulus, surface inertness and difficulty in grafting functional groups of titanium carbide flakes, it is extremely difficult to uniformly attach them to the surface of aramid fibers. Therefore, the present invention creatively utilizes the high viscosity of dopamine and its self-polymerization under alkaline conditions, adjusts the pH value of the system, and allows dopamine to form linear polymers through free radical polymerization, ultimately allowing the two-dimensional titanium carbide flakes to uniformly attach to the surface of the aramid fibers.
[0028] The beneficial effects of the present invention are:
[0029] (1) The present invention provides a method for preparing a flexible electromagnetic shielding material based on a composite of two-dimensional titanium carbide (MXene) and aramid fiber. The preparation process is simple. Thanks to the strong viscosity of dopamine polymer, the grafted MXene flakes are evenly distributed and not easy to fall off. It has good electrical conductivity and X-band electromagnetic shielding effectiveness.
[0030] (2) The present invention provides a method for preparing a flexible electromagnetic shielding material based on a composite of two-dimensional titanium carbide (MXene) and aramid fiber. The preparation process is simple, safe and environmentally friendly. It does not require the participation of toxic solvents and does not emit toxic gases / liquids. The waste liquid generated can be directly discharged after adjusting the pH.
[0031] (3) The present invention provides a method for preparing a flexible electromagnetic shielding material based on a composite of two-dimensional titanium carbide (MXene) and aramid fiber. The prepared aramid-MXene composite material has ultra-flexibility, high strength, and broadband high electromagnetic shielding effectiveness, and can be further processed into flexible electromagnetic shielding products of different forms. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1(a) A scanning electron microscope (SEM) image of the surface of the ultrasonically cleaned aramid fiber obtained in Example 2 of a method for preparing a flexible electromagnetic shielding material based on a composite of two-dimensional titanium carbide (MXene) and aramid fiber of the present invention; (b) A scanning electron microscope (SEM) image of the surface of the aramid fiber after dopamine surface modification obtained in Comparative Example 1.
[0033] Figure 2 (a) A scanning electron microscope (SEM) image of a layer of two-dimensional titanium carbide flakes uniformly attached to the surface of the aramid fiber obtained in Example 2 of the method for preparing a flexible electromagnetic shielding material based on a composite of two-dimensional titanium carbide (MXene) and aramid fiber of the present invention; (b) A scanning electron microscope (SEM) image after the titanium carbide coating was destroyed using high-power ultrasound (500W, 100mins) in water.
[0034] Figure 3 This is an X-ray energy dispersion spectrum of the titanium and carbon content ratios of the aramid-MXene composite material obtained in Example 2 of the method for preparing a flexible electromagnetic shielding material based on a composite of two-dimensional titanium carbide (MXene) and aramid fiber of the present invention.
[0035] Figure 4 X-ray energy dispersion spectrum of the aramid-MXene composite material obtained in Example 2 of the method for preparing a flexible electromagnetic shielding material based on a composite of two-dimensional titanium carbide (MXene) and aramid fiber of the present invention: (a) scanning diagram of titanium element content (overlapping with the scanning electron microscope image); (b) scanning diagram of carbon element content; (c) scanning diagram of titanium element content.
[0036] Figure 5: S21 measurement results of modified aramid fiber in an X-band waveguide after the aramid-MXene composite material obtained in Examples 1-5 of the preparation method of a flexible electromagnetic shielding material based on a composite of two-dimensional titanium carbide (MXene) and aramid fiber and Comparative Example 1 reacted with different titanium carbide concentrations (0~5 mg / mL).
[0037] Figure 6: The shielding effectiveness of the modified aramid fiber in the X-band waveguide after the aramid-MXene composite material obtained in Examples 1-5 and Comparative Example 1 of the preparation method of a flexible electromagnetic shielding material based on a composite of two-dimensional titanium carbide (MXene) and aramid fiber of the present invention was calculated based on the measurement results of S21 and S11 after the modified aramid fiber reacted with different titanium carbide concentrations (0~5 mg / mL). DETAILED DESCRIPTION
[0038] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally. Example 1
[0039] A method for preparing a flexible electromagnetic shielding material based on a composite of two-dimensional titanium carbide (MXene) and aramid fiber is as follows:
[0040] (1) Preparation of stable two-dimensional titanium carbide flakes dispersed in aqueous solution
[0041] (1.1) Take 1g of titanium aluminum carbide powder (100 um) and dry it in an oven at 100℃ for 24 hours, and prepare 10mL of mixed acid solution (6mL of 12M hydrochloric acid, 3mL of 49% hydrofluoric acid and 1mL of deionized water). Slowly add the dried titanium aluminum carbide to the mixed acid solution in a fume hood and react for 24 hours with vigorous stirring. After the reaction is completed, pour all the liquid into a plastic centrifuge tube and centrifuge at 3500 rpm for 2 minutes to separate the precipitate;
[0042] (1.2) Add 10 mL of deionized water to the precipitate, pour the mixture into a plastic centrifuge tube, centrifuge at 3500 rpm for 2 min, and remove the precipitate. Repeat this step six times, and the measured pH value is 6.5;
[0043] (1.3) Remove the precipitate, add 10 mL of an aqueous solution containing 20% lithium chloride, stir vigorously for 10 min in an ice-water bath, let stand for 4 hours, centrifuge at 3500 rpm for 2 min to separate the two-dimensional titanium carbide flakes dispersed aqueous solution, and finally adjust the concentration of the two-dimensional titanium carbide flakes dispersed aqueous solution to 1 mg / mL.
[0044] (2) Cleaning aramid fibers
[0045] 5 g of para-aramid fiber was ultrasonically cleaned with acetone solution, deionized water, and isopropanol for 5 minutes each, and then dried.
[0046] (3) Aramid fiber grafted two-dimensional titanium carbide (MXene) sheets
[0047] (3.1) Add 0.1 g of dopamine hydrochloride powder to 50 mL of deionized water to prepare a dopamine solution with a concentration of 2 mg / mL;
[0048] (3.2) 5 g of washed aramid fibers and 50 mL of a dispersed aqueous solution of two-dimensional titanium carbide flakes were added to 50 mL of a 2 mg / mL dopamine solution. Under magnetic stirring, an aqueous solution of tris(hydroxymethyl)aminomethane was added to raise the pH value of the mixed solution to 8. Finally, air was continuously introduced into the solution and the reaction was allowed to proceed for 24 hours.
[0049] (4) Washing the aramid fiber and drying it to make aramid-MXene composite material
[0050] The aramid fiber was taken out and rinsed repeatedly with clean water until no black residue flowed out. The washed fiber was dried in an oven at 80°C for 12 hours to obtain an aramid-MXene composite material.
[0051] The aramid-MXene composite material provided by the present invention was used to perform a strength test on the aramid-MXene fiber prepared in this embodiment using a strength tester, and a Key sight N9918A vector network analyzer and a Flann X-band waveguide were used to perform an electromagnetic shielding effectiveness test on the aramid-MXene fiber prepared in this embodiment (the aramid-MXene fiber was compressed in the waveguide with a thickness of 1 mm, and a time domain gate was used to eliminate multiple reflections). The results showed that the electromagnetic shielding effectiveness of the aramid-MXene fiber in the X-band exceeded 20 dB. Example 2
[0052] A method for preparing a flexible electromagnetic shielding material based on a composite of two-dimensional titanium carbide (MXene) and aramid fiber is as follows:
[0053] (1) Preparation of stable two-dimensional titanium carbide flakes dispersed in aqueous solution
[0054] (1.1) Take 1g of titanium aluminum carbide powder (100 um) and dry it in an oven at 100℃ for 24 hours, and prepare 10mL of mixed acid solution (4mL of 12M hydrochloric acid, 5mL of 49% hydrofluoric acid and 1mL of deionized water). Slowly add the dried titanium aluminum carbide to the mixed acid solution in a fume hood and react for 48 hours with vigorous stirring. After the reaction is completed, pour all the liquid into a plastic centrifuge tube and centrifuge at 5500 rpm for 3 minutes to separate the precipitate;
[0055] (1.2) Add 100 mL of deionized water to the precipitate, pour the mixture into a plastic centrifuge tube, centrifuge at 5500 rpm for 5 min, and remove the precipitate. Repeat this step six times, and the measured pH value is 6.5;
[0056] (1.3) Remove the precipitate, add 20 mL of an aqueous solution containing 20% lithium chloride, stir vigorously in an ice-water bath for 10 min, let stand for 4 hours, centrifuge at 5500 rpm for 5 min to separate the two-dimensional titanium carbide flakes dispersed aqueous solution, and finally adjust the concentration of the two-dimensional titanium carbide flakes dispersed aqueous solution to 2 mg / mL.
[0057] (2) Cleaning aramid fibers
[0058] 5 g of para-aramid fiber was ultrasonically cleaned with acetone solution, deionized water, and isopropanol for 5 minutes each, and then dried.
[0059] (3) Aramid fiber grafted two-dimensional titanium carbide (MXene) sheets
[0060] (3.1) Add 0.2 g of dopamine hydrochloride powder to 50 mL of deionized water to prepare a dopamine solution with a concentration of 4 mg / mL;
[0061] (3.2) 5 g of washed aramid fibers and 50 mL of a dispersed aqueous solution of two-dimensional titanium carbide flakes were added to 50 mL of a 4 mg / mL dopamine solution. A boric acid-sodium hydroxide aqueous solution was added under magnetic stirring to raise the pH value of the solution to 8.3. Finally, air was continuously introduced into the solution and the reaction was allowed to proceed for 48 hours.
[0062] (4) Washing the aramid fiber and drying it to make aramid-MXene composite material
[0063] The aramid fiber was taken out and rinsed repeatedly with clean water until no black residue flowed out. The washed fiber was dried in an oven at 100°C for 11 hours to obtain an aramid-MXene composite material.
[0064] The aramid-MXene composite material provided by the present invention was used to perform a strength test on the aramid-MXene fiber prepared in this embodiment using a strength tester, and a Key sight N9918A vector network analyzer and a Flann X-band waveguide were used to perform an electromagnetic shielding effectiveness test on the aramid-MXene fiber prepared in this embodiment (the aramid-MXene fiber was compressed in the waveguide with a thickness of 1 mm, and a time domain gate was used to eliminate multiple reflections). The results showed that the electromagnetic shielding effectiveness of the aramid-MXene fiber in the X-band exceeded 50 dB. Example 3
[0065] A method for preparing a flexible electromagnetic shielding material based on a composite of two-dimensional titanium carbide (MXene) and aramid fiber is as follows:
[0066] (1) Preparation of stable two-dimensional titanium carbide flakes dispersed in aqueous solution
[0067] (1.1) Take 1g of titanium aluminum carbide powder (100 um) and dry it in an oven at 100℃ for 24 hours, and prepare 10mL of mixed acid solution (3mL of 12M hydrochloric acid, 6mL of 49% hydrofluoric acid and 1mL of deionized water). Slowly add the dried titanium aluminum carbide to the mixed acid solution in a fume hood and react for 48 hours with vigorous stirring. After the reaction is completed, pour all the liquid into a plastic centrifuge tube and centrifuge at 2500 rpm for 20 minutes to separate the precipitate;
[0068] (1.2) Add 10 mL of deionized water to the precipitate, pour the mixture into a plastic centrifuge tube, centrifuge at 2500 rpm for 20 min, and remove the precipitate. Repeat this step six times, and the measured pH value is 6.5;
[0069] (1.3) Remove the precipitate, add 100 mL of an aqueous solution containing 20% lithium chloride, stir vigorously for 10 min in an ice-water bath, let stand for 24 hours, centrifuge at 2500 rpm for 20 min to separate the two-dimensional titanium carbide flakes dispersed aqueous solution, and finally adjust the concentration of the two-dimensional titanium carbide flakes dispersed aqueous solution to 3 mg / mL.
[0070] (2) Cleaning aramid fibers
[0071] 5 g of para-aramid fiber was ultrasonically cleaned with acetone solution, deionized water, and isopropanol for 5 minutes each, and then dried.
[0072] (3) Aramid fiber grafted two-dimensional titanium carbide (MXene) sheets
[0073] (3.1) Add 0.2 g of dopamine hydrochloride powder to 50 mL of deionized water to prepare a dopamine solution with a concentration of 4 mg / mL;
[0074] (3.2) 5 g of washed aramid fibers and 50 mL of a dispersed aqueous solution of two-dimensional titanium carbide flakes were added to 50 mL of a 2 mg / mL dopamine solution. A potassium hydrogen phosphate-citric acid aqueous solution was added under magnetic stirring to raise the pH value of the solution to 8.4. Finally, air was continuously introduced into the solution and the reaction was allowed to proceed for 48 hours.
[0075] (4) Washing the aramid fiber and drying it to make aramid-MXene composite material
[0076] The aramid fiber was taken out and rinsed repeatedly with clean water until no black residue flowed out. The washed fiber was dried in an oven at 120°C for 10 hours to obtain an aramid-MXene composite material.
[0077] The aramid-MXene composite material provided by the present invention was used to perform a strength test on the aramid-MXene fiber prepared in this embodiment using a strength tester, and a Key sight N9918A vector network analyzer and a Flann X-band waveguide were used to perform an electromagnetic shielding effectiveness test on the aramid-MXene fiber prepared in this embodiment (the aramid-MXene fiber was compressed in the waveguide with a thickness of 1 mm, and a time domain gate was used to eliminate multiple reflections). The results showed that the electromagnetic shielding effectiveness of the aramid-MXene fiber in the X-band exceeded 75 dB. Example 4
[0078] A method for preparing a flexible electromagnetic shielding material based on a composite of two-dimensional titanium carbide (MXene) and aramid fiber is as follows:
[0079] (1) Preparation of stable two-dimensional titanium carbide flakes dispersed in aqueous solution
[0080] (1.1) Take 1g of titanium aluminum carbide powder (100 um) and dry it in an oven at 100℃ for 24 hours, and prepare 10mL of mixed acid solution (8mL of 12M hydrochloric acid, 1mL of 49% hydrofluoric acid and 1mL of deionized water). Slowly add the dried titanium aluminum carbide to the mixed acid solution in a fume hood and react for 48 hours with vigorous stirring. After the reaction is completed, pour all the liquid into a plastic centrifuge tube and centrifuge at 1500 rpm for 60 minutes to separate the precipitate;
[0081] (1.2) Add 10 mL of deionized water to the precipitate, pour the mixture into a plastic centrifuge tube, centrifuge at 1500 rpm for 60 min, and remove the precipitate. Repeat this step six times, and the measured pH value is 6.5;
[0082] (1.3) Remove the precipitate, add 50 mL of an aqueous solution containing 20% lithium chloride, stir vigorously for 100 min in an ice-water bath, let stand for 24 hours, centrifuge at 1500 rpm for 60 min to separate the two-dimensional titanium carbide flakes dispersed aqueous solution, and finally adjust the concentration of the two-dimensional titanium carbide flakes dispersed aqueous solution to 4 mg / mL.
[0083] (2) Cleaning aramid fibers
[0084] 5 g of para-aramid fiber was ultrasonically cleaned with acetone solution, deionized water, and isopropanol for 5 minutes each, and then dried.
[0085] (3) Aramid fiber grafted two-dimensional titanium carbide (MXene) sheets
[0086] (3.1) Add 0.3 g of dopamine hydrochloride powder to 50 mL of deionized water to prepare a dopamine solution with a concentration of 6 mg / mL;
[0087] (3.2) 5 g of washed aramid fiber and 50 mL of a dispersed aqueous solution of two-dimensional titanium carbide flakes were added to 50 mL of a 6 mg / mL dopamine solution. Carmody buffer solution was added under magnetic stirring to raise the pH value of the solution to 8. Finally, air was continuously introduced into the solution and the reaction was allowed to proceed for 48 hours.
[0088] (4) Washing the aramid fiber and drying it to make aramid-MXene composite material
[0089] The aramid fiber was taken out and rinsed repeatedly with clean water until no black residue flowed out. The washed fiber was dried in an oven at 140°C for 9 hours to obtain an aramid-MXene composite material.
[0090] The aramid-MXene composite material provided by the present invention is used to perform a strength test on the aramid-MXene fiber prepared in this embodiment using a strength tester; a Key sight N9918A vector network analyzer and a Flann X-band waveguide are used to perform an electromagnetic shielding effectiveness test on the aramid-MXene fiber prepared in this embodiment (the aramid-MXene fiber is compressed in the waveguide with a thickness of 1 mm, and a time domain gate is used to eliminate multiple reflections). The results show that the electromagnetic shielding effectiveness of the aramid-MXene fiber in the X-band exceeds 80 dB. Example 5
[0091] A method for preparing a flexible electromagnetic shielding material based on a composite of two-dimensional titanium carbide (MXene) and aramid fiber is as follows:
[0092] (1) Preparation of stable two-dimensional titanium carbide flakes dispersed in aqueous solution
[0093] (1.1) Take 1g of titanium aluminum carbide powder (100 um) and dry it in an oven at 100℃ for 24 hours, and prepare 10mL of mixed acid solution (6mL of 12M hydrochloric acid, 3mL of 49% hydrofluoric acid). Slowly add the dried titanium aluminum carbide to the mixed acid solution in a fume hood and react for 24 hours with vigorous stirring. After the reaction is completed, pour all the liquid into a plastic centrifuge tube and centrifuge at 1000 rpm for 120 minutes to separate the precipitate;
[0094] (1.2) Add 100 mL of deionized water to the precipitate, pour the mixture into a plastic centrifuge tube, centrifuge at 1000 rpm for 120 min, and remove the precipitate. Repeat this step six times, and the measured pH value is 6.5;
[0095] (1.3) Remove the precipitate, add 5 mL of aqueous solution containing 20% lithium chloride, stir vigorously for 10 min in an ice water bath, let stand for 48 hours, centrifuge at 1000 rpm for 120 min to separate the two-dimensional titanium carbide flakes dispersed aqueous solution, and finally adjust the concentration of the two-dimensional titanium carbide flakes dispersed aqueous solution to 5 mg / mL.
[0096] (2) Cleaning aramid fibers
[0097] 5 g of para-aramid fiber was ultrasonically cleaned with acetone solution, deionized water, and isopropanol for 5 minutes each, and then dried.
[0098] (3) Aramid fiber grafted two-dimensional titanium carbide (MXene) sheets
[0099] (3.1) Add 0.4 g of dopamine hydrochloride powder to 50 mL of deionized water to prepare a dopamine solution with a concentration of 8 mg / mL;
[0100] (3.2) 5 g of washed aramid fiber and 50 mL of a dispersed aqueous solution of two-dimensional titanium carbide flakes were added to 50 mL of a dopamine solution having a concentration of 8 mg / mL. An aqueous solution of N-tris-(hydroxymethyl)methylaminoacetic acid was added under magnetic stirring to raise the pH value of the solution to 8.3. Finally, air was continuously introduced into the solution and the reaction was allowed to proceed for 48 hours.
[0101] (4) Washing the aramid fiber and drying it to make aramid-MXene composite material
[0102] The aramid fiber was taken out and rinsed repeatedly with clean water until no black residue flowed out. The washed fiber was dried in an oven at 160°C for 8 hours to obtain an aramid-MXene composite material.
[0103] The aramid-MXene composite material provided by the present invention was used to perform a strength test on the aramid-MXene fiber prepared in this embodiment using a strength tester, and a Key sight N9918A vector network analyzer and a Flann X-band waveguide were used to perform an electromagnetic shielding effectiveness test on the aramid-MXene fiber prepared in this embodiment (the aramid-MXene fiber was compressed in the waveguide with a thickness of 1 mm, and a time domain gate was used to eliminate multiple reflections). The results showed that the electromagnetic shielding effectiveness of the aramid-MXene fiber in the X-band exceeded 85 dB.
[0104] Comparative Example 1
[0105] A preparation method based on a comparison group of MAX phase two-dimensional titanium carbide (MXene) and aramid fiber composite materials is as follows:
[0106] (1) Cleaning aramid fibers
[0107] 5 g of para-aramid fiber was ultrasonically cleaned with acetone solution, deionized water, and isopropanol for 5 minutes each, and then dried.
[0108] (2) Aramid fiber grafted with dopamine
[0109] (3.1) Add 0.2 g of dopamine hydrochloride powder to 50 mL of deionized water to prepare a dopamine solution with a concentration of 4 mg / mL;
[0110] (2.2) 5 g of washed aramid fiber and 50 mL of deionized water were added to 50 mL of 4 mg / mL dopamine solution. Under magnetic stirring, an aqueous solution of trimethylolmethylaminopropanesulfonic acid was added to raise the pH value of the solution to 8.4. Finally, air was continuously introduced into the solution and the reaction was allowed to proceed for 24 hours.
[0111] (4) Washing the aramid fiber and drying it to make an aramid-dopamine composite material
[0112] The aramid fiber was taken out and rinsed repeatedly with clean water. The washed fiber was dried in an oven at 120° C. for 10 hours to obtain an aramid-dopamine composite material.
[0113] The electromagnetic shielding effectiveness of the aramid-dopamine fiber prepared in this embodiment was tested using a Key sight N9918A vector network analyzer and a Flann X-band waveguide (the aramid-dopamine fiber was compressed in the waveguide with a thickness of 1 mm, and a time domain gate was used to eliminate multiple reflections). The results showed that the aramid-dopamine fiber had almost no electromagnetic shielding effectiveness in the X-band (close to 0 dB).
[0114] Example MXene / aramid NW content (wt%) Shielding effectiveness (dB) Single filament breaking strength (cN / dtex) (GPa) Example 1 1% 20 4.1 Example 2 2% 50 4.1 Example 3 3% 75 4.1 Example 4 4% 80 4.0 Example 5 5% 85 4.0 Comparative Example 1 0% 0 4.2
[0115] Examples 3, 4, and 5 can achieve good electromagnetic shielding effects, and the single-filament breaking strength of the aramid fiber does not decrease significantly, indicating that the internal structure of the aramid fiber is stable and its structure is not changed in the chemical treatment of the examples.
Claims
1. A method for preparing a flexible electromagnetic shielding material based on a composite of two-dimensional titanium carbide and aramid fiber, characterized in that: Aramid fiber is used as a raw material for chemical modification and grafting of two-dimensional titanium carbide sheets, including the following steps: Step 1: Prepare a stable two-dimensional titanium carbide flake dispersion; Step 2: Cleaning the aramid fiber; Step 3: dissolving dopamine hydrochloride powder in water to prepare a dopamine hydrochloride solution of a certain concentration; Step 4: adding the washed aramid fiber and the two-dimensional titanium carbide flake dispersion to the dopamine hydrochloride solution, wherein the mass ratio of the two-dimensional titanium carbide to the aramid fiber is 1-5:100-500; Step 5: Add pH buffer to adjust the pH value of the system so that dopamine hydrochloride forms a linear polymer through free radical polymerization, and finally the aramid fiber is grafted onto the two-dimensional titanium carbide sheet; Step 6: Wash the aramid fiber and dry it to make an aramid-two-dimensional titanium carbide composite material; The electromagnetic shielding effectiveness of the aramid-two-dimensional titanium carbide composite material is between 20 and 85 dB in the X-band of 8.2 GHz to 12.4 GHz.
2. The preparation method according to claim 1, characterized in that: In step 1, titanium aluminum carbide powder is vigorously stirred in a mixed acid solution to react, and the precipitate is taken out by centrifugation; deionized water is added to the precipitate and then centrifuged again to wash the acid solution; lithium chloride aqueous solution is added to the precipitate, and it is vigorously stirred in an ice water bath, and finally centrifuged several times to make the pH greater than 6, and the upper clear liquid is taken to separate the two-dimensional titanium carbide flake dispersed aqueous solution.
3. The preparation method according to claim 2, characterized in that: The mixed acid solution is a mixed solution of 12M hydrochloric acid, 49% hydrofluoric acid and deionized water, the volume ratio of 12M hydrochloric acid, 49% hydrofluoric acid and deionized water is 3-8:1-4:1, the concentration of lithium chloride aqueous solution is 20%, and the ratio of titanium aluminum carbide powder, mixed acid solution and lithium chloride aqueous solution is 1g:100-200mL:500-1000mL.
4. The preparation method according to claim 2, characterized in that: The acid washing operation needs to be repeated by centrifugation five times or more until the pH value is between 6 and 7.
5. The preparation method according to claim 1, characterized in that: In step 2, the aramid fiber is para-aramid, meta-aramid or heterocyclic aramid; the cleaning method is to ultrasonically clean the aramid fiber with acetone, deionized water and isopropyl alcohol respectively, and then dry it.
6. The preparation method according to claim 1, characterized in that: In step three, dopamine hydrochloride powder is added to deionized water, and the concentration of the dopamine hydrochloride solution is 2 mg / mL.
7. The preparation method according to claim 1, characterized in that: In step 4, the concentration of the two-dimensional titanium carbide flake dispersion is 1-5 mg / mL, and the mass ratio of dopamine hydrochloride to two-dimensional titanium carbide is 2:1-5.
8. The preparation method according to claim 1, characterized in that: In step 5, pH buffer solution is added under magnetic stirring to raise the pH value of the solution to 8.2-8.5, and finally air is continuously introduced into the solution while maintaining strong stirring, and the reaction time is more than 24 hours.
9. The preparation method according to claim 8, characterized in that: The pH buffer solution is a tris(hydroxymethyl)aminomethane aqueous solution, a boric acid-sodium hydroxide aqueous solution, a potassium hydrogen phosphate-citric acid aqueous solution, a carmodylic buffer solution, an N-tris(hydroxymethyl)methylaminoacetic acid aqueous solution or a tris(hydroxymethyl)methylaminopropanesulfonic acid aqueous solution.
10. The preparation method according to claim 1, characterized in that: In step six, the aramid fiber is taken out and repeatedly rinsed with clean water for more than ten times until no black residue flows out; the drying temperature is 80-160° C. and the drying time is 8-12 hours.
Citation Information
Cited By
Multifunctional non-woven fabric coated PPy fiber fabric and preparation method and application thereof
CN121250677A
Preparation method and application of in-situ composite conductive aramid fiber
CN121629549A
